Value Networks For Competitive Advantage : A Study On NST Petrol Station - Mohd Ariff, Mohd Amir (2009)
This is a study on NST Petrol Station - which operates a service station owned by ExxonMobil - that aims to show that a service station can increase its business performance by focusing on its value networks, where capabilities, relationships and customer vakues are emphasised.